The Effect of Motivation, Discipline, Knowledge, and Skills on Ajwad Resto’s Employee Performance - Yan Wari Musthafa Zein; Risya Ladiva Bridha (Gastronomy Tourism Journal, 2022)
Tourism has several elements including restaurants. Good restaurants are generally characterized by quality human resources so that they are able to provide maximum performance. Among the factors that affect performance are motivation, discipline, knowledge, and skills. This study was aimed to determine the effect of motivation, discipline, knowledge, and skills on the performance of Ajwad Resto employees. Research that uses this quantitative method has a sample of 31 employees of Ajwad Resto. The sampling technique used is non-probability sampling with saturated sampling type. The data obtained in this study came from literature studies and field studies which included questionnaires, interviews, observations, and documentation. In this study, the analytical method used is the multiple linear regression method. The results of this study are motivation, discipline, knowledge, and skills partially and simultaneously have a positive effect on the performance of Ajwad Resto employees.